2020
DOI: 10.1038/s41598-020-60831-8
|View full text |Cite
|
Sign up to set email alerts
|

Interface Chemistry of Graphene/Cu Grafted By 3,4,5-Tri-Methoxyphenyl

Abstract: Chemical reaction with diazonium molecules has revealed to be a powerful method for the surface chemical modification of graphite, carbon nanotubes and recently also of graphene. Graphene electronic structure modification using diazonium molecules is strongly influenced by graphene growth and by the supporting materials. Here, carrying on a detailed study of core levels and valence band photoemission measurements, we are able to reconstruct the interface chemistry of trimethoxybenzenediazonium-based molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…This bonding position reforms the planar structure of the pristine rGO and results in wrinkled-paper-like morphology as observed in the TEM (Figure ) and STM (Figure ) results. Our synthesized material shows a nearly uniform distribution of PAP molecule over the rGO surface as reported in an earlier work of Bueno et al and Ambrosio et al, where they have shown that the organic molecule with amine functional groups tends to form covalent linkage over the graphene/graphite structure at the basal plane. , …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This bonding position reforms the planar structure of the pristine rGO and results in wrinkled-paper-like morphology as observed in the TEM (Figure ) and STM (Figure ) results. Our synthesized material shows a nearly uniform distribution of PAP molecule over the rGO surface as reported in an earlier work of Bueno et al and Ambrosio et al, where they have shown that the organic molecule with amine functional groups tends to form covalent linkage over the graphene/graphite structure at the basal plane. , …”
Section: Resultssupporting
confidence: 85%
“…Our synthesized material shows a nearly uniform distribution of PAP molecule over the rGO surface as reported in an earlier work of Bueno et al and Ambrosio et al, where they have shown that the organic molecule with amine functional groups tends to form covalent linkage over the graphene/graphite structure at the basal plane. 74,75 In this unique functionalized rGO-PAP, the free hydroxyl terminal group acts as an interaction site for the biomolecules. There are two possible ways to adsorb and connect the DA molecule with the rGO-PAP surface, which can be represented as type-1 and type-2 hydrogen (H) bonds as shown in Figure S5.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…5b and 5c) by following the procedure previously described. The recovery toward the initial energy position can be related to the molecule desorption that takes place at about 120°C 33,34 .…”
Section: Articlementioning
confidence: 99%
“…Graphene sheets are as thick as a carbon atom. The atoms in the graphene structure are combined with the sp 2 hybrid [21][22][23] . The mechanical properties of graphene are very interesting, which include the elastic modulus of 1 TPa and the fracture strength of 130 GPa 24,25 .…”
mentioning
confidence: 99%